PENGUNAAN METODE SERVQUAL PADA ANALISIS KUALITAS PELAYANAN UPTD PERLINDUNGAN SOSIAL DALAM PERLINDUNGAN ANAK TERLANTAR DI PROVINSI BANTEN - Syarifudin, Achmad; Ramadhani, Gigih; Wirawati, Sri Mukti (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2023)
UPTD adalah Unit Pelayanan Teknis Daerah. UPTD Perlindungan Sosial is to carry out operational technical activities of the Office in the field of Social Protection, as outlined in the "Banten Governor Regulation Number 19 of 2018 concerning the Establishment of Organization and Work Procedures of Service Branches and Regional Technical Implementation Units within the Banten Provincial Office. The purpose of public service is to increase public trust in the government. Purpose This study knows the extent of abandoned children's satisfaction and what services must be improved on the five dimensions of service qualityThe methods used are Service Quality (Servqual), Data Collection Methods in this study Observation, Documentation and Questionnaires with 15 attribute statements. Based on the results of Gap Servqual data processing, 3 (three) attributes were obtained which are included in improving service quality. The Assurance dimension on the attribute (X9) with a gap of -0.59, (X8) with a gap of -0.04 and the Responsiveness dimension on the attribute (X4) with a gap of -0.25.The conclusion of this study, there are still 2 dimensions with unfavorable results, namely the Assurance and Responsiveness dimensions. UPTD Perlindungan Sosial Banten Province is expected to consider proposed improvements using the 5W+1H that the researcher has provided.